Analysis of Financial Ratios on the Profitability of Islamic Commercial Banks in Indonesia: An Empirical Study in the Post-Transition Period 2022–2024 - M Ivan Julio Subastian; Rahmat Priyanto; Uun Sunarsih (STIE Tri Bhakti, 2026)
The independent variables examined include Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (BOPO), with Return on Equity (ROE) as the dependent variable. The study employs a panel data regression method using the Random Effect Model (REM) on 10 Islamic Commercial Banks with 30 observation units during the period of 2022–2024. The results indicate that simultaneously all variables significantly affect ROE (F-stat = 28.4512; p = 0.0000) with a coefficient of determination of 87.71%. Partially, only BOPO has a significant negative effect (? = ?0.5594; p = 0.0000), while CAR, NPF, and FDR do not show a significant effect during this period. These findings provide strategic implications for bank management to prioritize operational efficiency through service digitalization in order to maintain the stability of equity profitability in the post-consolidation era of Islamic banking in Indonesia.